In Vitro Fertilization(IVF) for Gilbert Syndrome Associated with ßeta-Thalassemia, A Case Report - Albu, Dragos; Albu, Alice; Bohiltea, Roxana (International Journal of Sciences: Basic and Applied Research (IJSBAR), 2021)
The Gilbert syndrome is a familial tip of a benign condition characterized by a high level of unconjugated bilirubin without hemolysis or liver disease. In this syndrome, there is a mutation of the UGT1A1 gene on the long arm (q) of chromosome 2, which synthesize the enzyme uridine diphosphate-glucuronosyltransferase-1A1 (UGT1A1), that conjugate bilirubin. Hepatic glucuronidation activity is diminished by 30%. The association between Gilbert syndrome and in vitro fertilization (IVF) is not yet presented in the literature. A 34-year-old nulliparous woman presented to our clinic for primary infertility. Antimullerian hormone level was normal: 3.5 ng/ml. Her partner sperm analysis showed severe oligoasthenoteratozoospermia: 5milion/ml concentration, 25 % progressive motility, 3% standard form. She was known for Gilbert syndrome and ßeta thalassemia. She decided to go for in vitro fertilization (IVF) with ICSI (intracytoplasmic sperm injection). We used a short antagonist protocol with letrozole 2.5mg twice a day and 150 UI menotropins to avoid estradiol rising, which could determine, in her case, the level of serum bilirubin to increase. We collected fourteen oocytes; twelve of them were in metaphase II, nine fertilized by ICSI, and we obtained three good blastocyst 4aa, 4ab, and 4ba (according to Gardner-Schoolcraft criteria). We transferred one blastocyst, and ß HCG was negative on day eleven after embryo transfer. Next month, we transferred on a natural cycle one blastocyst: 4ab after thawing. Ultrasound confirmed a single pregnancy with a heartbeat. In this Gilbert syndrome, to avoid estradiol rising, we used aromatase inhibitors in conjunction with gonadotropins for IVF ovarian stimulation.